IMPROVEMENT OF FARMERS SKILL AND HOUSEHOLD INCOME THROUGH APPLICATION OF CLEAN, INTEGRATED AND SUSTAINABLE PRODUCTION ON HORTICULTURE AND CASSAVA COMMODITIES - Mulyaningsih, Yanyan (Universitas Djuanda Bogor, 2016)
Sustainable plant cultivation is an effort to increase productivity by applying environmentallyfriendly technology and the efficiency of production facility utilization and product processingwith no or less waste or clean production. The objective of this activities are to improvefarmerâs skill in vegetable and cassava cultivation and processed them to half-process productinto food product which are highly nutritious, safe, and preferred by consumers. This activityinvolved Bojong and Sadar Tani Farmer Group at Bojongmurni Village, Ciawi District, BogorRegency. The method used are extension, training, assistance and establishment ofdemonstration plot. Materials provided include the manufacture of organic fertilizer andmocaf, cultivation technique of vegetables and cassava, processing mocaf to food product andsimple bookkeeping farming. Results showed that there was an improved awareness oftraining participants in the implementation of clean and sustainable production system inorder to increase their income. This was shown from their enthusiasm in applying theknowledge they got in the trainings in this community service program.